Algorithmic learning theory 22nd International Conference, ALT 2011, Espoo, Finland, October 5-7, 2011. Proceedings - Kivinen, Jyrki; Szepesvári, Csaba; Ukkonen, Esko.; Zeugmann, Thomas; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 22nd International Conference on Algorithmic Learning Theory, ALT 2011, held in Espoo, Finland, in October 2011, co-located with the 14th International Conference on Discovery Science, DS 2011. The 28 revised full papers presented together with the abstracts of 5 invited talks were carefully reviewed and selected from numerous submissions. The papers are divided into topical sections of papers on inductive inference, regression, bandit problems, online learning, kernel and margin-based methods, intelligent agents and other learning models.
Electronic reproduction.
Keywords: Computer science; Computer software; Logic design; Artificial intelligence; Electronic books